Thermoelectric Generator Modeling and Power Maximization in Non-Uniform Heat Distribution - Fauzan, Miftah Yama (Curtin University, 2021)
Thermoelectric generation (TEG) has become a promising alternative energy whose source comes from abundant thermal. The conversion method is environmentally friendly, since it is based on a physical process allowing direct conversion from thermal to electricity. Other advantages of the system include silent operation, no moving parts, long lifetime, and supporting the sustainability motto of “reduce, reuse, recycle”. This thesis provides a study of maximizing the power generation of thermoelectric generator considering non-uniform heat distribution.